Building a roadmap for developing combination therapies for Alzheimer's disease. (March 2014) - Perry, Daniel; Sperling, Reisa; Katz, Russell; Berry, Donald; Dilts, David; Hanna, Debra; Salloway, Stephen; Trojanowski, John Q; Bountra, Chas; Krams, Michael; Luthman, Johan; Potkin, Steven; et al.
<x xml:space="preserve">Abstract</x> Combination therapy has proven to be an effective strategy for treating many of the world's most intractable diseases. A growing number of investigators in academia, industry, regulatory agencies, foundations and advocacy organizations are interested in pursuing a combination approach to treating Alzheimer's disease. A meeting co-hosted by the Accelerate Cure/Treatments for Alzheimer's Disease Coalition, the Critical Path Institute and the Alzheimer's Association addressed challenges in designing clinical trials to test multiple treatments in combination and outlined a roadmap for making such trials a reality.